The Development of Ecoprint Media in Stimulating Creativity in Early Childhood - Ayunisa Ayunisa; Shofiyanti Nur Zuama; Amrullah Amrullah; Andi Agustiatih (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop ecoprint media to stimulate creativity in kindergarten. The method used in this study is Sugianto's R&D, which has been modified to produce specific products and test their effectiveness, as well as using the ADDIE development method, because this development model has advantages in its systematic process stages. Each phase is evaluated and revised from the stages that have been passed so that the resulting product is a valid product. In addition, the ADDIE model is very simple but its implementation is systematic. Data is collected through observation, surveys accompanied by interviews. Data is collected through observation, interviews, and expert validators. Media validation is carried out by media and material experts. Media effectiveness is measured through independent sample t-tests in media design. Data analysis uses qualitative and quantitative methods. The research results show that ecoprint media can stimulate children's creativity. This media is also considered to help teachers in helping children think creatively in solving problems and optimizing their potential. The innovation of ecoprint media is expected to help make the learning process more diverse and less monotonous for children.